«Being Only Then Begins to Be When It Is Threatened with Non-being»: In Search of Dostoevsky, or to the Anniversary of B.N. Tikhomirov - Dergacheva, I.V. (Âzyk i tekst, 2022)
This article, written for the anniversary of B.N. Tikhomirov, one of the most distinguished researchers of F.M. Dostoevsky, is an attempt to reflect the scale of his unique activity in popularizing the creative heritage of the great Russian writer. A huge achievement of the hero of the day is his selfless activity in systematizing and publishing autographs of F.M. Dostoevsky, a hermeneutic interpretation of his texts from the standpoint of the patristic Christian tradition and a description of the locus Petersburg text, reflecting the topography of the writer and his characters with jewelry accuracy. The special contribution of B.N. Tikhomirov introduced textual criticism into the editorial field by preparing real, mythopoetic, historical and literary commentaries on Dostoevsky's texts. Scientific thought of B.N. Tikhomirov covered every aspect of philological knowledge about the great Russian writer and his works, his works demonstrate the breadth of methodology and the variety of methods of literary analysis of Dostoevsky's literary and journalistic text, the historical and literary process of his time, fragments of literary life. Данная статья, написанная к юбилею Б.Н. Тихомирова, одного из самых заслуженных исследователей творчества Ф.М. Достоевского, является попыткой отразить масштаб его уникальной деятельности по популяризации творческого наследия великого русского писателя. Огромным достижением юбиляра является его подвижническая деятельность по систематизации и публикации автографов Ф.М. Достоевского, герменевтическое толкование его текстов с позиции святоотеческой христианской традиции и описание локусного петербургского текста, с ювелирной точностью отражающего топографию писателя и его героев. Особый вклад Б.Н. Тихомиров внес в эдиционную текстологию, подготовив реальные, мифопоэтические и историко-литературные комментарии к текстам Достоевского. Научная мысль Б.Н. Тихомирова охватила каждый аспект филологического знания о великом русском писателе и его произведениях, его работы демонстрируют широту методологии и разнообразие методик литературоведческого анализа художественного и публицистического текста Достоевского, историко-литературного процесса его времени, фрагментов литературной жизни.